2015
DOI: 10.1186/s12885-015-1781-0
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in the meibomian glands in patients with oral administration of anticancer combination drug-capsule TS-1®: a case report

Abstract: BackgroundThe anticancer TS-1® combination capsules of tegafur, gimeracil, and oteracil potassium (Taiho Pharmaceutical Co. Ltd, Japan) causes side effects, i. e., corneal epithelial disorder and dacryostenosis. However, its side effect on meibomian gland had not been reported. We observed morphological changes in the meibomian gland in patients taking TS-1® who exhibited punctate corneal epithelial defects to examine if dysfunction of meibomian glands is involved in the corneal epitheliopathy.Case presentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 10 publications
0
18
1
Order By: Relevance
“…However, it was suggested that systemic medication also could damage the gland or impair its secretory function. We reported patients with loss of meibomian glands with superficial punctate epitheliopathy during treatment of cancer with an anticancer TS-1 ® combination capsules of tegafur, gimeracil, and oteracil potassium (Taiho Pharmaceutical Co. Ltd, Japan) (Mizoguchi et al, 2015) (Fig. 2).…”
Section: Medication-related Meibomian Gland Diseasesmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it was suggested that systemic medication also could damage the gland or impair its secretory function. We reported patients with loss of meibomian glands with superficial punctate epitheliopathy during treatment of cancer with an anticancer TS-1 ® combination capsules of tegafur, gimeracil, and oteracil potassium (Taiho Pharmaceutical Co. Ltd, Japan) (Mizoguchi et al, 2015) (Fig. 2).…”
Section: Medication-related Meibomian Gland Diseasesmentioning
confidence: 99%
“…To address this issue, we developed a model of ocular surface alkali burn in C57BL/6 mice (Mizoguchi, 2015). Severe inflammation in ocular surface including lid margin epithelium is induced by an exposure to alkali.…”
Section: Chemical Burn In the Ocular Surface And Meibomian Glandmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we reported that inflammation associated with severe allergic conjunctivitis is associated with abnormal morphology of meibomian glands 3 . We also reported that conjunctival inflammation caused by systemic TS-1 anticancer therapy may cause obstruction of the gland orifice, leading to damage of the gland 4 . Because ocular surface alkali injury causes damage to both the conjunctiva and lid margin, leading to severe inflammation, it would seem likely that alkali injury may effect meibomian gland function either through direct damage to the meibomian gland, leading to scarring and plugging of the gland orifice or mediated through palpebral inflammation.…”
Section: Introductionmentioning
confidence: 79%